Electromechanical effects of concentric hypertrophy on the left ventricle: A simulation study. (1st August 2018) - Del Bianco, Fabrizio; Colli Franzone, Piero; Scacchi, Simone; Fassina, Lorenzo
Abstract: In this work, we analyze the way concentric hypertrophy, triggered by mild aortic stenosis, affects the electromechanical activity of the left ventricle during a cardiac cycle by employing a 3D finite-element strongly-coupled model. Three mechanical feedbacks on electrophysiology are considered: the conduction feedback, acting on conductivity tensors, the convection feedback, dependent on the deformation rate, and the mechanoelectric feedback due to stretch-activated membrane channels. In case of a multiple endocardial electrical stimulation for a healthy ventricle, the convection feedback raises the values of action potential duration APD while modifying the corresponding distribution patterns, mainly in the latest activated regions. Hypertrophy stresses the latter effect. If an endocardial ectopic stimulation is applied to the healthy ventricle, the convection feedback enhances its effects on APD (by increasing the corresponding dispersion too), especially on the opposite side with respect to the stimulation site; the mechanoelectric feedback reduces APD values on the midmyocardium instead. By including all feedbacks, it turns out that the hypertrophic ventricle exhibits lower values and a modified epicardial pattern of APD if compared with the healthy and stenotic (without growth) ventricles, but its transmural dispersion of repolarization does not increase and its epicardial electrograms have the same morphological features. Despite a decrease of the end-diastolic volume, hypertrophy compensates for the stenotic increase of the end-systolic volume and of the internal pressure during the efflux phase, while normalizing stroke work. Highlights: We analyze mechanical feedbacks and cardiac response under concentric hypertrophy. We employ a finite-element model with cardiac cycle, aortic stenosis and growth. The convection feedback always increases the action potential duration. The hypertrophic ventricle shows the lowest values of action potential duration. Hypertrophy counteracts stenosis by adjusting the ventricular pressure-volume loop.